The storage quality and transcriptome analysis of fresh-cut taro by L-ascorbic acid combined with ultrasonic treatment - Lin Chen; Bingzhi Chen; Lulu Chu; Lili Chen; Luyu Xie; Youjin Deng; Yuji Jiang (Ultrasonics Sonochemistry)
Fresh-cut taro, renowned for its high nutritional value and convenience, is prone to rapid browning post-cutting, which hinders its storage life. This study focused on the effects of L-ascorbic acid (AA) combined with ultrasound (US) treatment (AS) on the storage quality and transcriptome analysis of fresh-cut slices of Yongding June Red Taro. Compared to the control (CK) group, AS treatment effectively reduced the weight loss rate of taro slices, maintained higher hardness, delayed the increase of browning, and inhibited the accumulation of O2− and H2O2. Furthermore, the AS group showed increased glutathione levels and maintained higher activities of ascorbate peroxidase and glutathione reductase, yet decreased the contents of flavonoids and reducing sugars. Simultaneously, in the AS group, the activities of tyrosinase and lipoxygenase were lowered, thereby preserving the high sensory quality of fresh-cut taro slices. Transcriptome analysis revealed that differentially expressed genes (DEGs) between the AS and CK groups were annotated and categorized into 50 and 20 functional groups based on the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) databases, respectively. Notably, both groups exhibited significant enrichment in processes related to photosynthesis, protein processing in the endoplasmic reticulum, and isoflavone biosynthesis. Therefore, we concluded that AS treatment could alleviate oxidative stress and maintain storage quality by regulating metabolic pathways. These findings provide insights into the physiological changes occurring in taro immediately after cutting and serve as an essential basis for developing effective storage and preservation techniques.